Estimating groundwater availability using the electromagnetic very low frequency (EM-VLF) method - Diah Sabatini Sitiningrum; Hayati Sari Hasibuan; Yuki Mahardhito Adhitya Wardhana (Environmental and Materials, 2026)
Background: The coastal area of North Jakarta faces serious risks of groundwater table decline, seawater intrusion, and water quality degradation due to continuous groundwater extraction. Previous studies indicate that the aquifer system in North Jakarta consists of heterogeneous coastal alluvial deposits, including sand, silt, clay, and gravel. This condition causes groundwater potential to vary across locations. This study aims to analyze the potential availability of groundwater in Kalibaru Urban Village, Kampung Susun Akuarium Penjaringan, and Rusunawa Marunda. Methods: This study applied the Very Low Frequency Electromagnetic (EM-VLF) interpretation method to identify saturated zones beneath the surface. Field data included groundwater table depth, aquifer thickness, lithology, permeability factors, specific yield, salinity, and well measurements. Findings: The results show that Kalibaru Urban Village has the highest groundwater potential, with an aquifer zone depth of 12 to 45 m and an estimated discharge of 51.29 m³/day. Rusunawa Marunda also shows a groundwater-bearing zone at a depth of approximately 42 to 59 m. The variation in groundwater potential across the study sites is influenced by aquifer depth, aquifer thickness, lithological characteristics, specific yield, and salinity levels. Conclusion: Groundwater remains locally available in the three study sites. However, its use should be carefully limited because coastal areas are vulnerable to increased salinity, contamination, seawater intrusion, and a decline in the groundwater table. Government agencies and local communities need to strengthen groundwater level monitoring, water quality testing, pumping control, piped water services, and rainwater harvesting. Novelty/Originality of this article: This study provides an EM-VLF-based assessment of groundwater potential in three coastal locations in North Jakarta. It also connects subsurface technical findings with the need for site-specific groundwater management strategies.